Suppose that the functions \( q \) and \( r \) are defined as follows, \( \begin{array}{l}q(x)=-4 x+5 \\ r(x)=x+3 \\ \text { Find the following. } \\ (r \circ q)(2)=\square \\ (q \circ r)(2)=\square\end{array} \)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
The Deep Dive
To solve for \( (r \circ q)(2) \) and \( (q \circ r)(2) \), we first need to understand what these compositions mean. 1. **Calculating \( (r \circ q)(2) \)**: This means we first apply \( q \) to \( 2 \), and then apply \( r \) to the result. \[ q(2) = -4(2) + 5 = -8 + 5 = -3 \] Now, apply \( r \) to \( -3 \): \[ r(-3) = -3 + 3 = 0 \] So, \( (r \circ q)(2) = 0 \). 2. **Calculating \( (q \circ r)(2) \)**: Here, we apply \( r \) to \( 2 \) first, and then apply \( q \) to that result. \[ r(2) = 2 + 3 = 5 \] Now, apply \( q \) to \( 5 \): \[ q(5) = -4(5) + 5 = -20 + 5 = -15 \] So, \( (q \circ r)(2) = -15 \). Putting it all together, we have: \[ (r \circ q)(2) = 0 \] \[ (q \circ r)(2) = -15 \]